Modal extraction accuracy using Single Station Time Domain (SSTD) techniques / A. F. Ghazali and A. A. Mat Isa - Ghazali, A. F.; Mat Isa, A. A. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2012)
Single Station Time Domain (SSTD) technique is one of the efficient methods used to extract modal parameters. This technique relies on free decay responses to obtain the required parameters. In this paper, a study on time shift interval on SSTD algorithm method is investigated. It is found that altering specific time interval settings could improve the accuracy of natural frequencies and damping ratios determination of a structure. Accuracy assessment of the method is made using simulated analytical data with known properties where percentage error between the results of simulated and this method can be calculated and compared.